Effective Antimicrobial Activity of Green ZnO Nano Particles of Catharanthus roseus - Gupta, Monika; Tomar, Rajesh S.; Kaushik, Shuchi; Mishra, Raghvendra K.; Sharma, Divakar (Frontiers in Microbiology, 2018)
In the present study, zinc oxide nanoparticles (ZnO NPs) were synthesized using leaf extract of Catharanthus roseus under different physical parameters. Biosynthesis of ZnO NPs was confirmed by UV-Visible spectrophotometer and further, characterized by X-Ray Diffraction (XRD), Fourier Transform Infrared spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Energy-Dispersive X-ray spectroscopy (EDX), Atomic Force Microscopy (AFM), Photoluminescence study and Dynamic Light Scattering (DLS). We have also confirmed that several physical parameters such as pH, temperature, the concentration of metal ions and reaction time were able to regulate shape and size of synthesized ZnO NPs. XRD and TEM analysis provided the information about the average size and hexagonal morphology of ZnO NPs, respectively. FTIR spectra analysis suggested that phenolic compounds played a crucial role in the biosynthesis of ZnO NPs. The significant antibacterial activity of ZnO NPs was observed against Staphylococcus aureus MTCC 9760, Streptococcus pyogenes MTCC 1926, Bacillus cereus MTCC 430, Pseudomonas aeruginosa MTCC 424, Proteus mirabilis MTCC 3310 and Escherichia coli MTCC 40. The synthesized ZnO NPs have shown antibacterial efficacy against both Gram-positive and Gram-negative pathogens. Synergistic effects of ZnO NPs and streptomycin showed increased efficacy as indicated by the increased zone of clearance in comparison to their individual effects (either ZnO NPs or streptomycin). Overall, the results elucidated a rapid, cost-effective, environmentally friendly and convenient method for ZnO NPs synthesis, which could be used as a potential antimicrobial agent against drug-resistant microbes.